Extraction of Papain from Papaya (Carica papaya L.) Fruit Latex and Its Application in Transforming Tannery Raw Trimming - Olyad Erba Urgessa; Duguma Dibbisa Itana; Tamiru Oljira Raga (Ethiopian Journal of Science and Sustainable Development, 2019)
The leather industry is one of the major polluting industries in Ethiopia. Environment protection has prompted industrialists and scientists to re-look at transformation of tannery solid waste materials to valuable products using enzymatic hydrolysis. Acid and liming process of gelatin production generate large amount of wastes and used limited raw materials.  This study was therefore, aimed to extract papain from papaya fruit latex and use it for transforming raw trimming to gelatin. Extraction and purification was carried out using Three Phase Partitioning. Protein content and protease activity were determined using lowry and casein hydrolysis method, respectively. Effect of agitation time taken, crude extract to t-butanol ratio, ammonium sulphate concentration and temperature on purification fold and activity recovery of papain was evaluated and process was optimized. At its optimized parameters, the intermediate phase of TPP showed 94.14% percentage of protease activity recovery and 8.31 purification fold. At its optimized parameters, bottom phase showed 75.15% percentage of protease activity recovery and 6.61 purification fold. Enzymatic hydrolysis of raw trimming produced 68 wt% and 64 wt% gelatin recovery from the use of crude and intermediate phase papain, respectively. Relatively low gel strength of gelatin with bloom value of 95g and 87g were obtained from hydrolysis of raw trimming by intermediate and crude papain, respectively. This study showed that the use of crude extract for transforming raw trimming to gelatin was found good as it showed comparable protease activity. The TPP can be employed for the extraction and purification of proteases from papaya fruit for industrial application that requires it in partial pure form.